Management Information System and Organizational Success in a Competitive Environment: A Study of Small Scale Businesses in Port Harcourt - Nwachukwu Precious Ikechukwu; Ake Okechukwu; Benjamin Erastus; Sopirinye Ezekiel Epelle (International Journal of Engineering and Management Research, 2019)
The purpose of this paper was to examine the effect of management information system as a process for improving organizational success: A case study of small scale businesses in port Harcourt. The research design was descriptive survey to study and observe the influence of management information system in organizational success in a competitive environment. It is very important for managers of small scale businesses within this expanse to effectively install a management information system that will constantly provide them with update on the currents in their environment, both internally and externally since this will help them to make strategic decisions that will have an impact on the success or failure of the organization. Findings from the research shows that when an organization is equipped with a sound management information system, it tends to enjoy improved customer services, increased adaptability, production improvement, improved management decision making process etc. Consequently, it is very important for managers to take the competitive environmental factors seriously since it can affect the operations and performance of the business both internally and externally .Some recommendations were put forward to resolve some of the issues of the research.